Does Eco-Efficiency Improve Financial Performance of Manufacturing Companies in Indonesia? - Meutia, Inten; Ramadhani, Marini; Adam, Mohamad (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
This study aims to determine the impact of environmental performance proxied by eco-efficiency on the financial performance of manufacturing companies in Indonesia. n this study, the multiple linear regression test was used to analyse the data. The sample of this study is manufacturing companies that listed at the Indonesia Stock Exchange from 2012 until 2016 with the total observation is 80 firm-years.The results of this study indicated that the average level of eco-efficiency of the manufacturing companies is still relatively low (0.38). The environmental performance as measured by the eco-efficiency has a positive significant effect on the financial performance of the companies. Therefore, this study suggests that companies can improve their financial performance by enhancing their eco-efficiency level.This study aims to determine the impact of environmental performance proxied by eco-efficiency on the financial performance of manufacturing companies in Indonesia. n this study, the multiple linear regression test was used to analyse the data. The sample of this study is manufacturing companies that listed at the Indonesia Stock Exchange from 2012 until 2016 with the total observation is 80 firm-years.The results of this study indicated that the average level of eco-efficiency of the manufacturing companies is still relatively low (0.38). The environmental performance as measured by the eco-efficiency has a positive significant effect on the financial performance of the companies. Therefore, this study suggests that companies can improve their financial performance by enhancing their eco-efficiency level.